Phenotype-genotype relationships in complementation group 3 of the peroxisome-biogenesis disorders. - Chang, C C (1998)
The peroxisome-biogenesis disorders (PBDs) are a set of often lethal genetic diseases characterized by mental retardation and defective peroxisomal matrix protein import. Mutations in PEX12 are known to underlie the disease in two patients from complementation group 3 of the PBDs. Here we show that all patients from this group carry mutations on both alleles of PEX12. A comparison between PEX12 genotypes and the clinical and cellular phenotypes of the corresponding PBD patients suggests a relatively straightforward relationship between genotype and phenotype in this group of the PBDs, such that the loss of PEX12 function leads to more-severe cellular and clinical phenotypes. However, one patient who presented relatively mild clinical and cellular phenotypes was a compound heterozygote for two seemingly severe mutations on each PEX12 allele. PEX12 mRNA present in the patient's cells was derived from only one allele, the one that carried a 2-bp deletion early in the PEX12 coding region, c.26,27Delta. The deduced protein product of this mRNA would contain only the first eight amino acids of the protein, and yet this mutant PEX12 cDNA displayed significant PEX12 activity in a functional complementation assay. Surprisingly, the PEX12/c.26, 27Delta cDNA directed the synthesis of a 29-kD PEX12 protein in vitro, a result that is consistent with translation initiation at a downstream AUG codon. Transfection studies confirmed the expression of similarly sized PEX12 proteins from the PEX12/c.26,27Delta allele. Thus, it appears that translation initiation at internal AUG codons may modulate disease phenotypes and should be considered whenever unexpectedly mild phenotypes result from severe mutations early in the coding region.